Institutional mechanisms for screening foreign direct investments in EU member states - Kucheriavenko, Serhii (Problems of legality, 2026)
The article is devoted to a comprehensive study of the procedure for screening foreign direct investment in the European Union and the approaches of member states to determining the institutional organisation of the body authorised to assess risks and make decisions. The relevance of the issue raised is confirmed by statistical indicators: currently, all 27 member states of the European Union have either already had a screening mechanism in place, made changes to their procedures, adopted new relevant legislation, or initiated the process of introducing screening in the future. Despite the recommended guidelines set out in Regulation (EU) 2019/452, which regulates the screening procedure at the European Union level, the specifics of the screening procedure are individual in each country and depend on a number of different factors. Accordingly, the key research question was: what institutional models of competent authorities have been formed in the European Union, how are the functions between investigation and decision-making distributed among them, and what does this mean for the implementation of common economic security objectives within national procedures? To achieve the research goal, the objectives and subject focus of foreign direct investment screening were outlined, the requirements of Regulation (EU) 2019/452 for national competent authorities and the cooperation mechanism were analysed, and criteria for classifying institutional models of national screening authorities were identified. The empirical basis of the study is the author's dataset, which reflects the institutional design of national foreign direct investment screening mechanisms in European Union member states within the meaning of Regulation (EU) 2019/452. Methodologically, the study combines comparative institutional and legal analysis with doctrinal interpretation of legal norms. The article concludes with conclusions presenting a conceptual vision of the characteristic features of institutional models for the organisation of foreign direct investment screening in European Union member states, as well as proposed guidelines that can be taken into account by legislators when developing a national screening system.